Japanese automobile conglomerates in Indonesia: Knowledge transfer within an industrial cluster in the Jakarta Metropolitan Area - Hans-Dieter Evers; Farah Purwaningrum (University of Bonn, Center for Development Research (ZEF), 2013)
Foreign direct investment is supposed to stimulate economic growth through the transfer of new technical knowledge and product innovation. This paper deals with the knowledge flow within the Japanese automotive supply chain catalysed by the keiretsu network in Indonesia. For this purpose, we analyse the character of the keiretsu and we trace how the knowledge flow is managed via the vertical linkage between manufacturers and suppliers within an industrial cluster. By doing so, we intend to contribute to the growing literature on industrial upgrading of the global production network and the use of knowledge for innovation and development. Based on our qualitative study, we show that the process of industrial upgrading is cumbersome for the automotive supplier companies in Indonesia. This is partly due to the fiscal incentive based policy of the Indonesian government and at the micro level due to the keiretsu as an institution, whereby knowledge flow is mediated by the restrictive practices of the supplier development programme.
Keywords: 330; Japan; Indonesia; keiretsu; automotive supply chain; institution; innovation; knowledge management; government automotive policy; supplier development programme